2007
DOI: 10.1002/cvde.200706624
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Temperature PECVD of Nanodevice‐Grade nc‐3C‐SiC

Abstract: In this work, we report a plasma-based synthesis of nanodevice-grade nc-3C-SiC films, with very high growth rates (7-9 nm min -1 ) at low and ULSI technology-compatible process temperatures (400-550°C), featuring: (i) high nanocrystalline fraction (67 % at 550°C); (ii) good chemical purity; (iii) excellent stoichiometry throughout the entire film; (iv) wide optical band gap (3.22-3.71 eV); (v) refractive index close to that of single-crystalline 3C-SiC; and (vi) clear, uniform, and defect-free Si-SiC interface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…However, with the increased hydrogen dilution ratio X, the C-based weak or strained near-surface bonds (such as sp 2 C or sp 3 C) are more easily and effectively etched away from the growth surface by the hydrogen radicals compared to the Si-based strained bonds (such as sp 3 Si). 36,37 In addition to this, the C-based radicals have a lower sticking coefficient than the Si-based radicals. 21 These considerations explain the experimental results that smaller numbers of carbon atoms are incorporated into the films at a higher value of X.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, with the increased hydrogen dilution ratio X, the C-based weak or strained near-surface bonds (such as sp 2 C or sp 3 C) are more easily and effectively etched away from the growth surface by the hydrogen radicals compared to the Si-based strained bonds (such as sp 3 Si). 36,37 In addition to this, the C-based radicals have a lower sticking coefficient than the Si-based radicals. 21 These considerations explain the experimental results that smaller numbers of carbon atoms are incorporated into the films at a higher value of X.…”
Section: Discussionmentioning
confidence: 99%
“…Physical mechanisms for the effective crystallization of nanocrystalline silicon or nanocrystalline cubic silicon carbide in high-density inductively coupled plasmas completely without hydrogen precursor gas or at low hydrogen dilution ratios X have been investigated previously. 14,31,36,39…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was shown that low-frequency (460 kHz) inductively coupled plasma (ICP) CVD possesses a number of advantages for the fabrication of nanostructured silicon carbide films [17][18][19][20][21][22]. The low-frequency ICP system working in the H-mode discharge features low plasma sheath potentials at the deposition substrate, provides an independent control of the ion/radical fluxes and ion-bombarding energy and makes it possible to generate quiescent and stable plasmas with densities 1-2 orders of magnitude higher than in capacitive discharges [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Growth of the Single crystalline SiC films is usually realized only at high growth temperature greater than 1000 C [3]. owing to the lattice mismatch (20%) and the difference in the thermal expansion coefficient (8%) between SiC and Si, it is quite likely generating a residual stress and a high density of interface defects when the processing temperatures are very high [4]. However, several applications can benefit from heteroepitaxial system.…”
Section: Introductionmentioning
confidence: 99%